Gingival and alveolar ridge overgrowths: A histopathological evaluation from Saudi Arabia - Ibrahim Olajide Bello; Ahmed Qannam (Elsevier, 2022)
Background: Focal tissue overgrowths on the gingiva and edentulous alveolar ridge are occasionally perplexing to periodontists, owing to the wide variety of differential diagnoses that may be responsible. As such, biopsy and microscopy are often required to establish a definitive diagnosis. The present study aimed to retrospectively evaluate focal gingival and alveolar ridge overgrowths at a single institution in Saudi Arabia. Materials and Methods: Histopathology reports and slides from patients presenting to King Saud University Hospital between 1984 and 2016, particularly those with focal gingival enlargements other than those due to gingivitis and periodontitis, were collected and analyzed based on age, sex, and location. Results: A total of 624 patient records were evaluated, with a mean age of 35 years (range, 1 week-91 years), peak incidence in the third decade of life, male-to-female ratio of 1:1.4, and a slightly higher prevalence of lesions in the mandible. The majority (88%) of the lesions were reactive or hyperplastic, followed by malignant (10%) and benign (2%) tumors. A total of 24 distinct histological entities were diagnosed across the three groups. The most common histologically diagnosed lesions were pyogenic granulomas (38%), fibromas (33%), peripheral ossifying fibromas (9%), squamous cell carcinomas (7%), peripheral giant cell granulomas (6%), neurofibromas (1%), and non-Hodgkin lymphomas (1%). Conclusion: Similar to what has been reported by most previous studies, reactive hyperplastic lesions were the most prevalent focal overgrowths found in the gingival and alveolar mucosae. Carcinomas at these sites, however, may be an understated but significant clinical and epidemiological problem in Saudi Arabia. Gingival and alveolar ridge lumps can serve as a nexus for cooperation between periodontologists and oral pathologists to improve diagnosis, disease classification, and patient management.